Serialization in popular culture - Allen, Rob, 1976-; Berg, Thijs van den, 1977- (New York ; London : Routledge, 2014)
'From prime-time television shows and graphic novels to the development of computer game expansion packs, the recent explosion of popular serials has provoked renewed interest in the history and economics of serialization, as well as the impact of this cultural form on readers, viewers, and gamers. In this volume, contributors--literary scholars, media theorists, and specialists in comics, graphic novels, and digital culture--examine the economic, narratological, and social effects of serials from the nineteenth to the twenty-first century and offer some predictions of where the form will go from here.'--
Includes bibliographical references and index.
Keywords: Mass media and culture; Serial publications